National environmental policies and multilateral trade rules - Marion Jansen; Alexander Keck (World Trade Organization (WTO), 2004)
This paper provides an overview of institutional, economic and legal aspects of the relationship between national environmental policies and the multilateral trading system. In particular, it analyses some of the difficulties the WTO Dispute Settlement System faces when having to evaluate disputes on national environmental policies that have an impact on trade. From an economist's point of view it would be desirable that optimal environmental policies, i.e. policies that correct existing market failures, be ruled consistent with multilateral trade law. This paper argues that WTO law in theory provides appropriate tools to ensure rulings that are consistent with economic thinking. Yet, the paper also argues that economists have a rather imperfect knowledge of the precise welfare effects of different types of environmental policies. In practice, therefore, it is questionable whether economists are able to give adequate guidance to legal experts when it comes to the evaluation of national environmental policies. This is one of the reasons why there continues to be some degree of uncertainty as to the possible interpretations of certain WTO rules in the context of environmental disputes.
Keywords: F18; K33; Q58; 330; environmental policy; international trade; national treatment; WTO